WORD FORMATION ANALYSIS FOUND IN ENGLISH SLANGS USED BY JUSTIN BIEBER ON INSTAGRAM - Prastikawati, Entika Fani; Pratama, Febi Gilang; Wiyaka, Wiyaka (Institut Agama Islam Negeri Ponorogo, 2021)
This study aimed to find out the word-formations in English slang utilized on Instagram captions posted by Justin Bieber. This study applied a descriptive qualitative method to capture the process of word-formation in Justin Bieber’s English slang. In this study, the writers used the theory of Yule about the word-formation process for analyzing the data of English slang. The writers obtained the data through reading, capturing, and understanding the captions posted during a year (June 2020 – June 2021). Based on the data analysis, seven out of ten types of word-formation processes in English slang were used by Justin Bieber in his Instagram caption. They are (1) Clipping, (2) Blending, (3) Acronym, (4) Borrowing, (5) Derivation, (6) Coinage, and (7) Multi Processes. The most frequent type of word formation process used by Justin Bieber on Instagram is clipping with the 47 data’s frequency (54%). This study implies that Justin Bieber frequently used clipping to make short the words on every posted video or photo so his followers can easily understand his feeling.